1974
DOI: 10.1021/ac60340a010
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-potential mechanism for the potentiometric response of the sodium tungsten bronze electrode to dissolved oxygen and in chelometric titrations

Abstract: tions of complexing agents, the solution conditions are not constant, so that the chemical reaction, whose rate may depend on the structure of the electrode-solution interface, may cause different potential shifts at different concentrations of complexing agents. Consequently, the results of such studies should be treated with some caution. It is possible to obtain unambiguous results by using concentrations low enough so that the chemical reaction does not exert a significant effect on the half-wave potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Although it has been found that an AgCl film spontaneously precipitates upon simply immersing silver in 1−2 M KCl solution, no films are formed in saturated KCl solution . The resulting potential will be a mixed potential, which is observed when two or more simultaneously proceeding oxidation and reduction reactions are involved in exhibiting a potential at the electrode/electrolyte interface. ,, Because the current and potential of each contribution are related with the Butler−Volmer equation, the electrode potential settles at a potential under the zero total current condition. It is evident that it is not an equilibrium state.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been found that an AgCl film spontaneously precipitates upon simply immersing silver in 1−2 M KCl solution, no films are formed in saturated KCl solution . The resulting potential will be a mixed potential, which is observed when two or more simultaneously proceeding oxidation and reduction reactions are involved in exhibiting a potential at the electrode/electrolyte interface. ,, Because the current and potential of each contribution are related with the Butler−Volmer equation, the electrode potential settles at a potential under the zero total current condition. It is evident that it is not an equilibrium state.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a potentiometric sensor provides a direct measurement of the oxygen concentration, independent of the diffusion situation inside the sensor and the analyte. Different potentiometric sensors for dissolved oxygen have been realized based on sodium tungsten bronzes [ 6 , 7 ], antimony [ 8 ], copper [ 9 , 10 ], cobalt [ 11 , 12 ], and ruthenium oxide [ 13 ] as material for the indicator electrode. Among them, most promising is the usage of copper and cobalt electrodes because of their applicability in neutral pH media and up to air-saturated oxygen concentrations as well as the availability of these metals in microfabrication technology.…”
Section: Introductionmentioning
confidence: 99%
“…Lipophilic ionic additives were not added to membranes to avoid the mixed potential response [15,16].…”
Section: Chemical Membranesmentioning
confidence: 99%